Ứng dụng trí tuệ nhân tạo trong thiết kế học liệu microlearning cho học phần rèn luyện nghiệp vụ sư phạm trong đào tạo sinh viên ngành Giáo dục tiểu học - Phạm Thị Quỳnh Anh, Phạm Thị Quỳnh Anh; Ngô Thị Kim Hoàn, Ngô Thị Kim Hoàn (Tạp chí Giáo dục, 2026)
The 2018 General Education Curriculum highlights professional qualities and digital competence as essential for primary school teachers, creating an urgent need to renew teacher-training approaches in the digital transformation era. Microlearning supports this shift by delivering short, focused learning units, while artificial intelligence (AI)-especially generative AI-offers strong potential to automate and enhance instructional design. This study proposes an AI-supported process for developing microlearning materials for the Pedagogical Skills Training course in the Primary Education program at Hanoi Metropolitan University. Using document analysis and synthesis, the paper introduces a four-step framework: defining learning objectives, generating draft materials with AI, pedagogical refinement by lecturers, and deploying finalized resources on digital platforms. Examples of animated videos, infographics, and podcasts illustrate the model. Findings show that AI reduces technical workload, diversifies learning materials, and supports personalized pathways, while lecturers remain central in ensuring accuracy and pedagogical quality. The proposed process offers a scalable approach to strengthening digital competence in teacher education.